6,7-dihydroxy-3-phenylcoumarin inhibits thromboplastin induced disseminated intravascular coagulation - YARAT, AYŞEN; AKBAY, TUĞBA (WILEY, 2004)
6,7-Dihydroxy-3-phenylcoumarin (DHPC) was tested to determine whether it had any effect on vitamin K inhibition, by investigating the prothrombin time (PT), activated partial thromboplastin time (APTT), fibrinogen level and platelet count. The anticoagulant and antithrombotic effects of DHPC were compared with those of warfarin by conducting a 4 h acute trial on thromboplastin-induced disseminated intravascular coagulation (DIC), investigating various haemostatic and antioxidant system parameters and performing a haemogram. Of most significance was that in the 5-d DHPC trial on healthy controls, PT, APTT, fibrinogen, platelet count remained within normal levels. In the 4-h DIC trial, both DHPC (0.025 mg/kg, i.v.) and warfarin (0.25 mg/kg, i.v.) significantly inhibited DIC, by reducing the PT, APTT, and fibrin degradation products and increasing fibrinogen levels and platelet count. In the DIC drug groups, lipid peroxidation significantly increased only in the warfarin group and glutathione significantly increased only in the DHPC group. However leucocyte count was significantly higher in the DHPC than the warfarin group. Further investigation is required for why DHPC is effective on the parameters investigated, at doses one-tenth of those of warfarin.
Keywords: disseminated intravascular coagulation; 6,7-dihydroxy-3-phenylcoumarin; warfarin; glutathione; lipid peroxidation; TISSUE THROMBOPLASTIN; OXIDATIVE STRESS; WARFARIN THERAPY; RATS; INITIATION; ENDOTOXIN